ANALYSIS OF REGIONAL REGULATION ON GENERAL MINING SECTOR (MINERAL AND COAL) - DARSA PERMANA (Indonesian Mining Journal, 2010)
As Law No. 22 Year 1999 on Regional Government was implemented and then renewed by Law No. 32 Year 2004 on the same subject, all autonomous areas have issued various regional regulations, including that on general mining (mineral and coal). This is in line with the requirement of all autonomous areas for authority in managing their own regions based on the autonomy principles. After one decade since the regulation was applied, evaluation conducted by the government revealed that regional regulation in the general mining sector oriented mostly on increasing regional revenue without taking into consideration the existing legal principles. Surveys on 8 provinces showed similar facts, and the condition led to an unconducive business climate that could hinder the economic growth and the regions’ investment opportunity.